Cardiac involvement in patients with thalassemia major and control group: a case-control study - Toba Kazemi (Tehran University Medical Journal, 2018)
Background: The most common cause of death in thalassemic patients is cardiac involvement especially cardiomyopathy. If the early stages of heart disease in people with thalassemia are diagnosed, mortality of patients reduced significantly. In this case-control study we compare the clinical symptoms, signs and para-clinic finding in thalassemia patients with control group. Methods: In this case-control study, thalassemia patients who had visited in special clinic of Vali-e-Asr hospital of Birjand University Medical Sciences during January of 2013 to May of 2014 compared with normal subjects. They matched by age and sex. After explaining the aims of the project, the written consent was received from both groups. Clinical examinations including history taking and auscultation of heart and lungs were performed by Pediatrician. Moreover, using the standard methods, the measurement of height, weight and blood pressure were performed. In following, electrocardiography (ECG) was taken in both groups. Also, both groups underwent transthoracic echocardiography by one cardiologist. Results: 42 thalassemia patients and 42 healthy subjects was compared in this study. Dyspnea was the only different symptom in the two groups. (23.8% in case and 4.8% in control P=0.01) In physical examination respiratory rate (RR) is only higher in patients with thalassemia that controls, but heart rate (HR), abnormal heart and lung sounds were not different significantly between two groups. In ECG, PR interval and QTc interval in patients with thalassemia was longer than healthy subject. In echocardiography, ejection fraction was lower but left ventricular end-diastolic diameter (LVEDD), left ventricular end-systolic diameter (LVESD) and size of the right ventricle and pulmonary artery pressure (PAP) was significantly higher than those in the control group. Conclusion: According the result of this study, dyspnea was higher in patients with thalassemia from normal subjects and PR interval and QT interval was longer in thalassemic patients. As well as the size of the left ventricle, size of right ventricle, pulmonary artery pressure were higher than normal population. Also, LV ejection fraction was lower in thalassemia than normal population.